Optical Properties of Laboratory and Ambient Biomass Burning Aerosols: Elucidating Black, Brown, and Organic Carbon Components and Mixing Regimes. Issue 9 (6th May 2019) - Romonosky, Dian E.; Gomez, Samantha L.; Lam, Jared; Carrico, Christian M.; Aiken, Allison C.; Chylek, Petr; Dubey, Manvendra K.
Abstract: Biomass burning (BB) is an important global source of aerosol and trace gases that degrade air quality, decrease visibility, and impact climate and human health. Refractory black carbon (rBC), brown carbon (BrC), and organic aerosol are major components of BB emissions. BB aerosol composition is highly variable at the source and depends on fuel composition and combustion phase. Atmospheric aging alters fresh BB aerosol through processes that are complex and dynamic. To better understand the variability in optical properties, we report fresh aerosol laboratory measurements from burning southwestern U.S. fuels and compare them to aged ambient BB aerosol from wildfires over a range of atmospheric time scales. Our BB aerosol analysis uses the relationship between the absorption Ångström exponent and single‐scattering albedo (SSA) to identify rBC, BrC, and organic aerosol‐dominated regimes that are defined using Mie theory. This model framework is used to interpret the large variability in optical properties measured in laboratory burns. In contrast, we find the observed absorption Ångström exponent‐SSA relationship for ambient BB aerosol to be less variable and more clustered together with increased atmospheric aging. This transition from fresh to aged behavior is attributed to the homogenization of the BB aerosol from mixing and aging over several hours. Finally, BB aerosol in ambient fire plumes that have aged for several hours exhibits larger SSAs than laboratory flaming burns. We conclude that BrC/OC mixtures play a larger role than rBC in the positive climate forcing of BB aerosol than what would be projected from laboratory results. Key Points: A semiempirical Mie theory framework can be used to classify the chemical composition of biomass burning aerosol by optical properties Smoke optical properties in aged ambient fire plumes are more clustered and less variable than fresh laboratory burns due to mixing and aging Aerosols from ambient fires are shifted toward the brown carbon and organic carbon mixing regime relative to those from laboratory fires